2024
DOI: 10.1098/rstb.2023.0110
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year soundscape recordings and automated call detection reveals varied impact of moonlight on calling activity of neotropical forest katydids

Laurel B. Symes,
Shyam Madhusudhana,
Sharon J. Martinson
et al.

Abstract: Night-time light can have profound ecological effects, even when the source is natural moonlight. The impacts of light can, however, vary substantially by taxon, habitat and geographical region. We used a custom machine learning model built with the Python package Koogu to investigate the in situ effects of moonlight on the calling activity of neotropical forest katydids over multiple years. We prioritised species with calls that were commonly detected in human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…However, we performed additional empirical checks on several random recordings from the area and noted promising outcomes—few FPs and few missed calls, and high confidence (scores close to 1.0) for most TPs. Further, in a related study [ 73 ], large-scale analyses of multi-year recordings were performed using the trained model from this study, and daily calling patterns (inferred based on reported detections) of several species were found to be in close agreement with prior knowledge.…”
Section: Discussionsupporting
confidence: 57%
“…However, we performed additional empirical checks on several random recordings from the area and noted promising outcomes—few FPs and few missed calls, and high confidence (scores close to 1.0) for most TPs. Further, in a related study [ 73 ], large-scale analyses of multi-year recordings were performed using the trained model from this study, and daily calling patterns (inferred based on reported detections) of several species were found to be in close agreement with prior knowledge.…”
Section: Discussionsupporting
confidence: 57%
“…Symes et al . [ 50 ] investigate the effects of moonlight, and Do Nascimento et al . [ 51 ] of habitat structure on their calling activity.…”
Section: The Contributions To Four Technological Approaches In This T...mentioning
confidence: 99%